Fighting for survival: The experiences of lesbian, gay, bisexual, transgender, and questioning students in religious colleges and universities. Issue 1 (2nd January 2017) - Craig, Shelley L.; Austin, Ashley; Rashidi, Mariam; Adams, Marc
ABSTRACT: Little is known about the experiences of lesbian, gay, bisexual, transgender, and questioning (LGBTQ) students attending religious colleges and universities. This study used grounded theory to analyze the narratives ( N = 271) of LGBTQ former and current students. The central theme described by LGBTQ students was a fight for survival with five subthemes: (a) institutionalized homo/transphobia (strict school policies, enforcement of heterosexuality and gender conformity through discipline, conversion therapy); (b) a culture of fear (fear of exposure, homophobic panic and code words, seeking cover); (c) marginalization and isolation; (d) struggle (suffering and suicide, reconciling faith and LGBTQ identity); and (e) coping and resilience (surviving through critical thinking and strategic activism). Implications for practice are provided.